2002
DOI: 10.1126/science.1073308
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Postendocytic Sorting of G Protein-Coupled Receptors

Abstract: Recycling of the mu opioid receptor to the plasma membrane after endocytosis promotes rapid resensitization of signal transduction, whereas targeting of the delta opioid receptor (DOR) to lysosomes causes proteolytic down-regulation. We identified a protein that binds preferentially to the cytoplasmic tail of the DOR as a candidate heterotrimeric GTP-binding protein (G protein)-coupled receptor-associated sorting protein (GASP). Disruption of the DOR-GASP interaction through receptor mutation or overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
342
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(364 citation statements)
references
References 37 publications
21
342
1
Order By: Relevance
“…Therefore, JM4, JWA, and GTRAP3-18 might comprise a family of proteins that interact not only with CCR5, but also with other GPCRs or transmembrane-spannning proteins. Other GPCR-interacting proteins such as b-arrestins or members of the family of GPCR-associated sorting proteins (GASP) have been shown to bind and regulate not only one specific but several GPCR proteins [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, JM4, JWA, and GTRAP3-18 might comprise a family of proteins that interact not only with CCR5, but also with other GPCRs or transmembrane-spannning proteins. Other GPCR-interacting proteins such as b-arrestins or members of the family of GPCR-associated sorting proteins (GASP) have been shown to bind and regulate not only one specific but several GPCR proteins [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, MOR is uncapable of interacting with GASP and rapidly recycles back to the plasma membrane after activation [45]. Exchanging the cytoplasmic tail of DOR with that of MOR swapped the postendocytic sorting profiles of the receptors [44,46]. Therefore, we used these chimeric receptors (DORMT, DOR with the C-terminal tail of MOR, and MORDT, MOR with the C-terminal tail of DOR) to test whether different endocytic and postendocytic behaviors of the receptors are linked to the regulation of BACE1 and γ-secretase.…”
Section: Postendocytic Sorting Of Activated Dor Defines β-And γ-Secrementioning
confidence: 99%
“…lular trafficking. It has been reported that binding of GPCR-associated sorting protein (GASP) to the DOR cytoplasmic tail modulates lysosomal sorting of activated DOR [44]. On the contrary, MOR is uncapable of interacting with GASP and rapidly recycles back to the plasma membrane after activation [45].…”
Section: Postendocytic Sorting Of Activated Dor Defines β-And γ-Secrementioning
confidence: 99%
“…Receptor-associated proteins play important roles during receptor endocytosis and intracellular trafficking. A number of proteins that bind to the MOPr have been recently identified and functionally characterized [12][13][14][15][16]. We have previously identified and characterized a novel MOPr-interacting protein, the membrane glycoprotein M6a, which interacts with the MOPr and plays a role in receptor endocytosis in transfected human embryonic kidney 293 (HEK293) cells [17].…”
Section: Introductionmentioning
confidence: 99%